Genetic Differentiation and Origin of Naturalized Rainbow Trout Populations From Southern Chile, Revealed by the mtDNA Control Region Marker - Colihueque, Nelson; Estay, Francisco J.; Crespo, Julio E.; Arriagada, Aldo; Baessolo, Luisa; Canales-Aguirre, Cristian B.; Marín, Javier; Carrasco, René (Frontiers in Genetics, 2019)
Numerous self-sustaining naturalized or introduced populations of rainbow trout (Oncorhynchus mykiss) are widely distributed throughout the freshwaters of southern Chile. In this study, analysis of the mitochondrial DNA control region (CR) marker was conducted to investigate the level of genetic divergence among populations and their phylogenetic relationships with respect to native lineages. This information provided a framework to interpret the genetic structure and origin that was shaped during historical trout introduction efforts. To this end, we analyzed eleven naturalized populations of lakes and rivers from five basins. The CR marker revealed five haplotypes. The overall haplotype (H) and nucleotide (Π) diversities were 0.684 ± 0.030 and 0.00460 ± 0.00012, respectively. Global FST was 0.169, with several pairwise FST estimates showing significant differences (P < 0.05). The exact test of population differentiation corroborated this result (P < 0.001). Significant geographic structure was found (P < 0.05), with variations explained primarily by differences within populations (61.65%) and among group basins (20.82%). Maximum likelihood phylogenetic analysis resolved two distinct clades with medium bootstrap support when naturalized populations were aligned in conjunction with reference native lineages. The haplotype network revealed a close association between naturalized populations and four main haplotypes representative of three native ecotypes or lineages from western North America (rainbow trout, steelhead trout and redband trout). These results indicate a genetic population structuring for naturalized rainbow trout from southern Chile and an origin probably represented by multiple lineages sources. Thus, mitochondrial DNA data strongly suggest that stocking of rainbow trout from different origins may have occurred during or after the initial introduction efforts.